1984
DOI: 10.1159/000145864
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Aging Human Umbilical Artery and Vein

Abstract: Qualitative and quantitative changes in the human umbilical artery and vein were observed in 15 human specimens at different stages of development. Features such as intimal thickening and cellular lipid accumulation were found in umbilical vasculature. Cellular origin and quantification of lipid-containing cells were determined by electron microscopy. Within 1 month after birth, lipid-containing cells originating from macrophages were observed in the umbilical artery, while those originating from smooth muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
1
8
1
Order By: Relevance
“…It was reported that sparse collagen fibers were found, but almost no elastic fibers in the media layer was observed (9). Our study also confirmed this.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…It was reported that sparse collagen fibers were found, but almost no elastic fibers in the media layer was observed (9). Our study also confirmed this.…”
Section: Discussionsupporting
confidence: 91%
“…An important feature of the umbilical arteries media layer at this time was the increase in rough endoplasmic reticulum content. However, in a previous study a decrease in the amount of rough endoplasmic reticulum and glycogen was reported in the arterial media layer at twenty-five week (9). The important finding of our research was the increase in rough endoplasmic reticulum content and the amount of glycogen in the venous media layer at twenty-five week.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Dire consequences also follow spontaneous rupture of a venous varix. Postnatally, umbilical arteries were found to contain lipid in SMCs W. E. Stehbens and macrophages, although anorexia and reduced £ow could contribute to these changes [58,59]. Impaired umbilical artery £ow whether from degeneration, trauma, or increased placental vascular resistance may contribute to retarded fetal development.…”
Section: Umbilical Vesselsmentioning
confidence: 99%